(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This paper analyzes how sustainable environmental policy can strengthen a state’s international economic position by enhancing competitiveness, attracting investment, and securing long run growth. Drawing on recent evidence on green industrial policy, environmental governance, green trade, and natural capital investment, the study synthesizes global best practices and mechanisms linking environmental sustainability with economic performance [1–7]. The analysis shows that stringent yet well designed environmental regulations, green industrial policy, and investments in natural capital can coexist with – and often reinforce – economic growth, export competitiveness, and resilience, particularly when combined with technological innovation, strong institutions, and international cooperation [1–7]. International trade in environmental goods, adoption of green technologies, and alignment with the Sustainable Development Goals (SDGs) further improve a country’s reputation, access to markets, and bargaining power in global value chains [1,3,6,8]. However, policy incoherence, weak governance, and unbalanced prioritization of short term growth over environmental sustainability remain critical barriers [1,6,9]. The paper proposes an integrated framework in which environmental policy, green industrial strategy, and trade policy are jointly designed to maximize both ecological and economic returns, thereby consolidating the state’s international economic standing.